Structural analysis of mitochondrial rRNA gene variants identified in patients with deafness - Vila-Sanjurjo, Antón; Mallo, Natalia; Elson, Joanna L.; Smith, Paul M.; Blakely, Emma L.; Taylor, Robert W. (Frontiers in Physiology, 2023)
The last few years have seen dramatic advances in our understanding of the structure and function of the mammalian mito-ribosome. At the same time, the first attempts to elucidate the effects of mito-ribosomal fidelity (decoding accuracy) in disease have been made. Hence, the stage is ready for an attempt to push an important frontier in our understanding of mitochondrial genetics, this is, the elucidation of the phenotypic effects of mtDNA variants affecting the functioning of the mito-ribosome. Here, we have assessed the structural and functional role of all mt-rRNA variants presumably associated to deafness, including those located at non-conserved positions. Our analysis has used the highest-quality structural description of the human mito-ribosome currently available, together with a new understanding of the phenotypic manifestation of mito-ribosomal-associated variants. Basically, any base change capable of inducing a fidelity phenotype may be considered non-silent. Under this light, out of the previously reported 93 mt-rRNA variants, presumably associated to deafness, 49 were potentially non-silent. We also dismissed a large number of reportedly pathogenic mtDNA variants as polymorphisms. These results drastically update our view on the implication of the primary sequence of mt-rRNA in the etiology of deafness and mitochondrial disease in general. Our data shed much needed light on how mt-rRNA variants located at non-conserved positions may lead to mitochondrial disease and, most notably, provide evidence of the effect of haplotype context in the manifestation of some mt-rRNA variants.